2018
DOI: 10.1080/23288604.2018.1440347
|View full text |Cite
|
Sign up to set email alerts
|

Association Between User Fees and Dropout from Methadone Maintenance Therapy: Results of a Cohort Study in Vietnam

Abstract: Vietnam launched methadone maintenance therapy (MMT) in 2008 with donor funding. To expand and ensure sustainability of the program, Vietnam shifted the responsibility for financing portions of MMT to provinces and, in 2015, some provinces started collecting user fees for MMT. This study assesses the association between user fees and patient dropout using a one-year observational cohort of 1,021 MMT patients in which three of seven provinces included in the study implemented user fees. We also estimate the cat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
14
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(14 citation statements)
references
References 25 publications
0
14
0
Order By: Relevance
“…The majority of studies were conducted in the United States of America (n = 25) [33, 34, 37, 39, 40, 47, 50, 54, 56, 58, 61, 62, 64, 68-72, 75, 79, 82, 84, 86, 88, 93], China (n = 14) [31, 36, 45, 57, 65-67, 80, 90, 92, 94-97], Canada (n = 9) [42,46,52,53,74,77,78,87,89] and Europe (n = 9) [32,38,41,43,48,51,55,59,73]. The remaining studies were spread across Asia (n = 5) [60,81,83,85,91], Israel (n = 3) [35,75,76], India (n = 1) [49], Australia (n = 1) [44] and Africa (n = 1) [63].…”
Section: Study Characteristicsmentioning
confidence: 99%
See 1 more Smart Citation
“…The majority of studies were conducted in the United States of America (n = 25) [33, 34, 37, 39, 40, 47, 50, 54, 56, 58, 61, 62, 64, 68-72, 75, 79, 82, 84, 86, 88, 93], China (n = 14) [31, 36, 45, 57, 65-67, 80, 90, 92, 94-97], Canada (n = 9) [42,46,52,53,74,77,78,87,89] and Europe (n = 9) [32,38,41,43,48,51,55,59,73]. The remaining studies were spread across Asia (n = 5) [60,81,83,85,91], Israel (n = 3) [35,75,76], India (n = 1) [49], Australia (n = 1) [44] and Africa (n = 1) [63].…”
Section: Study Characteristicsmentioning
confidence: 99%
“…The most frequently used measure of dropout was time to discontinuation of OST (n = 32), with varying thresholds applied to identify date of dropout. Almost half the studies reporting on time to discontinuation did not specify a threshold for identifying dropout (n = 13) [37,40,42,43,45,56,62,65,68,69,85,91,94]; seven studies indicated that a patient was identified as having dropped out of OST if they missed more than 30 consecutive days of treatment [53,57,60,67,74,80,92]; six studies applied a threshold of seven days [44,46,49,78,96,97], and the remaining studies applied a threshold of five days [83], ten days [51], 14 days [58,66,95], 21 days [63]and two months [59]. The other six studies reporting on dropout used a binary measure, which identified patients as having dropped out of treatment after a specific period of follow-up [38,48,55,61,79,88].…”
Section: Study Characteristicsmentioning
confidence: 99%
“…Previous studies showed that apart from culture factors and medical costs of MMT, older age was negatively associated with QoL ( Smith and Larson, 2003 ). In Vietnam, patients had to pay for consumables, that is, US$130/year ( Johns et al, 2018 ), but not for medications while under treatment. The reason behind this is that according to the government policy, all Methadone medications are covered in the insurance-covered drug list.…”
Section: Discussionmentioning
confidence: 99%
“…In 2008, rst methadone program was pilot tested in six clinics in Vietnam. Since then, MAT was quickly scaled up nationwide, by mid-2015 being provided by more than 180 facilities and covering approximately 35000 patients in 50 provinces [39]. By March 01, 2017, 280 MAT clinics across the country were providing treatment for 51318 patients [40].…”
Section: Vietnammentioning
confidence: 99%
“…PWID receive methadone for free, but have to pay for laboratory tests before MAT initiation. In a number of provinces, MAT programs collect fees from patients in order to cover costs; this co-payment places signi cant nancial burden on patients and negatively in uences MAT access and adherence [39]. Only one site in Ho Chi Minh City provides buprenorphine because of its high costs compared with methadone.…”
Section: Vietnammentioning
confidence: 99%